The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1063/1.4928453
|View full text |Cite
|
Sign up to set email alerts
|

Separation of sperm and epithelial cells based on the hydrodynamic effect for forensic analysis

Abstract: In sexual assault cases, forensic samples are a mixture of sperm from the perpetrator and epithelial cells from the victim. To obtain an independent short tandem repeat (STR) profile of the perpetrator, sperm cells must be separated from the mixture of cells. However, the current method used in crime laboratories, namely, differential extraction, is a time-consuming and labor-intensive process. To achieve a rapid and automated sample pretreatment process, we fabricated a microdevice for hydrodynamic and size-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…One area where microfluidic devices have particularly excelled is the separation of sperm cells from samples with a low concentration of sperm cells relative to other material, including the separation of sperm from epithelial cells for forensic analysis, from white blood cells in contaminated semen, and from testicular cells after a testicular biopsy. Liu and coworkers developed a microfluidic system ( Figure 2 ) for the separation of sperm and epithelial cells for rapid forensic analysis ( 61 ). By designing a microchannel with functional structures, the hydrodynamic interaction between fluid flow and cells led to the separation of different sized cells.…”
Section: Microfluidics For Sperm Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…One area where microfluidic devices have particularly excelled is the separation of sperm cells from samples with a low concentration of sperm cells relative to other material, including the separation of sperm from epithelial cells for forensic analysis, from white blood cells in contaminated semen, and from testicular cells after a testicular biopsy. Liu and coworkers developed a microfluidic system ( Figure 2 ) for the separation of sperm and epithelial cells for rapid forensic analysis ( 61 ). By designing a microchannel with functional structures, the hydrodynamic interaction between fluid flow and cells led to the separation of different sized cells.…”
Section: Microfluidics For Sperm Sortingmentioning
confidence: 99%
“… This figure depicts a microfluidic system designed for rapid separation of sperm from epithelial cells with application in forensics related to sexual assaults. (A) A picture of the actual device; (B) the cell mixture is aligned against the top wall in the pinched segment, and then the position difference of different sized cells is amplified in the expansion region; (C) sperm recovery rate is improved in the parallel capillary tubes ( 61 ). …”
Section: Microfluidics For Sperm Sortingmentioning
confidence: 99%
“…Therefore, this method does not rely on sperm motility and can be used for selecting nonmotile sperms from other species. Liu et al used a modified version of PFF to separate a mixture of epithelial cells (with 40–60 µm diameter representing the victim's cells) from human sperm heads (with 4–6 µm diameter representing the perpetrator's cells) with the potential application in sexual assault and forensic medicine . However, numerical and experimental results conducted by Berendsen et al demonstrated that PFF alone could not be used to separate a mixture of sperms with flagellar (tails) from 11 µm microbeads.…”
Section: Continuous‐flow Microfluidics In Artmentioning
confidence: 99%
“…These issues can result in lack of reproducibility, inefficient cell separation, and delayed processing-which can contribute to lagging backlogs. Several rapid and/or automated methods for differential separation of sperm cells have been developed as faster alternatives, including the use of alkaline plate-based methods [12], laser microdissection [13,14], antibodybased cell capture [15,16] and microdevice-based methods [17][18][19]; unfortunately, these techniques have not been widely adopted as they are either too laborious and complex or are not yet commercially available.…”
Section: Introductionmentioning
confidence: 99%